2019
DOI: 10.1002/cbm.2112
|View full text |Cite
|
Sign up to set email alerts
|

The crime, mental health, and economic impacts of prearrest diversion of people with mental health problems: A systematic review

Abstract: BackgroundPrearrest diversion strategies are being adopted across the Western world, enabling the police to identify and divert people suspected of having mental disorder towards health and community services rather than the criminal justice system.AimsTo quantify longer‐term criminal justice and mental health outcomes after prearrest diversion of people with suspected mental disorder and consider economic correlates.MethodsA systematic review of published literature on longer term outcomes after prearrest div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…A systematic review in 2013 found that, whilst generally seen as a positive addition to services by local agencies and service users, the actual impact of L&D services on mental health outcomes and reoffending had been subject at best to methodologies that were only moderately rigorous and not to high quality research studies (Scott, McGilloway, Dempster, Browne, & Donnelly, 2013). This picture was confirmed in more recent systematic reviews (Kane, Evans, & Shokraneh, 2018; Schucan Bird & Shemilt, 2019). The most recent review also highlighted the need for future research and funding strategies to build in high‐quality, systematic evaluation of outcomes before implementing a theoretically attractive strategy more widely (Schucan Bird & Shemilt, 2019).…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…A systematic review in 2013 found that, whilst generally seen as a positive addition to services by local agencies and service users, the actual impact of L&D services on mental health outcomes and reoffending had been subject at best to methodologies that were only moderately rigorous and not to high quality research studies (Scott, McGilloway, Dempster, Browne, & Donnelly, 2013). This picture was confirmed in more recent systematic reviews (Kane, Evans, & Shokraneh, 2018; Schucan Bird & Shemilt, 2019). The most recent review also highlighted the need for future research and funding strategies to build in high‐quality, systematic evaluation of outcomes before implementing a theoretically attractive strategy more widely (Schucan Bird & Shemilt, 2019).…”
Section: Introductionsupporting
confidence: 62%
“…This picture was confirmed in more recent systematic reviews (Kane, Evans, & Shokraneh, 2018; Schucan Bird & Shemilt, 2019). The most recent review also highlighted the need for future research and funding strategies to build in high‐quality, systematic evaluation of outcomes before implementing a theoretically attractive strategy more widely (Schucan Bird & Shemilt, 2019).…”
Section: Introductionsupporting
confidence: 62%
“…There are various types of diversion programs, and studies on the application and effectiveness of diversion programs are limited and fragmented, particularly on the practice in low and middle income countries (Hayhurst et al , 2015; Schucan Bird and Shemilt, 2019). At the present time, there is no clarity on when and how diversion can occur at each of the various stages of the justice process and how justice-led diversion processes can and should engage the mental health-care system.…”
Section: Introductionmentioning
confidence: 99%
“…The crisis intervention team will assess the situation and transport the person in a specialized center for further psychiatric evaluation. Systematic reviews, however, report mixed findings about the capability of crisis intervention teams to connect people in crisis with community resources and prevent the use of force (Kane et al, 2018;Schucan Bird & Shemilt, 2019;Taheri, 2016).…”
Section: Introductionmentioning
confidence: 99%